(untitled) (Journal of Academic Research, 2021)
This study dealt with the environmental accounting disclosure in the business environment in the city of Misurata, where the focus was on studying the impact of both the level of environmental awareness of officials, and the impact of environmental measurements of the cost systems that applied in industrial companies on the quality of accounting information. The data obtained by questinair, 80 questinnairs were valid for analysis. The statistical Obtaining 80 valid questionnaires for analysis, and statistical analysis was were conducted on them using the statistical programs (SPSS, and Smart pls3) to test the study hypotheses. The study concluded that there is awareness among management officials of the importance of environmental accounting measurement, which plays a positive role in the quality of accounting information. As for cost systems of environmental measurement. Meanwhile, the study concluded there is a shortcoming of cost environmental measurement in cost systems. there are shortcomings in containing the costs of environmental activities.